Developing a Serious Game to Enhance Prevention and Phishing Awareness - Serkes, Denys; Svoboda, Jaroslav; Kolář, Vojtěch; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
The primary objective of this thesis is to develop a serious game aimed at raising awareness about phishing and educating users on how to avoid it. The theoretical part explores the concept of serious games, examining their definition, effectiveness, and successful applications. An initial game concept was developed and used to identify and analyse similar games, which informed the creation of the final concept. This final concept includes a detailed description of the game’s storyline, visuals, functionalities, and levels. A list of features was compiled and prioritised using the MoSCoW method, distinguishing between those implemented during the thesis and those reserved for future development. The practical part outlines the game’s development process, beginning with a description of the chosen tools—specifically the Unity game engine and the C\# programming language. Development was divided into two phases: a low-fidelity prototype and a high-fidelity prototype. The low-fidelity prototype involved designing the user interface, implementing game functionality, and creating basic visuals. The high-fidelity prototype focused on refining visuals and improving the interface. After development, the game underwent two types of evaluation. First, its visual and functional quality was assessed through user interviews. Testers provided feedback on what they liked, disliked, and suggested improvements. Second, the game’s educational effectiveness was evaluated through a questionnaire consisting of eight phishing-related questions. Each participant completed the questionnaire both before and after playing the game. The results, presented in a bar chart, showed a 33.33\% increase in correct responses on the second attempt, highlighting the game’s potential as an effective educational tool. Finally, all user feedback was analysed, and the identified improvements were implemented in the final version of the game.
Vedoucí práce: Jaroslav Svoboda
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses